REGIONAL DEMOCRATIZATION: A COMPARATIVE ANALYSIS OF EU AND US EFFORTS IN CENTRAL ASIA AND SOUTHEAST ASIA (Journal of International Studies, 2023)
The EU and US are established liberal democratic powers, having a shared political and intellectual tradition. As such, the promotion ofdemocracy is critical to their foreign policies in areas they deem to be of strategic importance to their core interests. Further, the EU and its democratization efforts as part of its foreign policy and strategic interests can be viewed through the ‘Fortress Europe’ concept and hegemonic stability theory. For the EU and the US, Central Asia and Southeast Asia are the major areas for democracy promotion efforts, respectively. Through a qualitative analysis of related EU and US policies published in open sources and organized according to the logic of the democratization process, EU and US democratization efforts could be characterized as an oscillation between core interests and values promotion. This was attributed to the loss of appeal due to socio-political-economic issues in the EU and the US, combined with a relative lack of success, and competition between entrenched elite power structures and alternative political ideologies. The critical point is that both the regions of Central Asia and Southeast Asia are postcolonial areas in which Western democracy efforts are being realized through the existing structural level for spreading “soft power” to influence internal policy. The key findings for both regions are being interpreted from the postcolonial perspective: “democratization” is the process that needs to be revised as some cultural and metropolitan dominance in both regions prevails in everyday social life. For example, the power of the Russian language in Central Asia does not make regional elites follow the democratic rights of the indigenous population struggling for their national identity in a postcolonial era, as Central Asian elites and society do not wish to examine the current Russia-Ukraine conflict in the region. In the case of Southeast Asia, the area was not influenced by communism at the level Central Asia was. The area is quickly adaptable to the external (in this case, the US) democratization efforts for making a society with liberal values and multicultural diversity that makes them different from other Asian countries. Moreover, the English language in the region is more often associated with access to the best education and Western values.